Priority areas of support for small and medium-sized enterprises within the framework of innovation policy - S. V. Simonov; V. S. Osipov (Управление)
The introduction of innovations is one of the main economic goals, since it is the main factor in ensuring the fulfillment of the tasks of import substitution, expanding economic expansion in foreign markets, and increasing the competitiveness of the domestic economy as a whole. Proceeding from this, the task of studying innovative processes in the domestic economic field is an urgent task. At the same time, special attention should be paid to the sector of small and medium-sized enterprises, since small organizations are able to respond more flexibly to market requirements and have less inertia in solving problems of quickly adjusting production to new rules. The small size of an enterprise determines the need for high efficiency of innovative spending, in contrast to larger and self-sufficient economic formations. Based on this, it is advisable to conduct a comparative analysis of the effectiveness of R&D in the SME sector with data on the economy as a whole in order to determine the priority vector of state support. In the course of the study, using mathematical and statistical methods, analysis, and synthesis. A conclusion has been made about the applicability of the method for determining the effectiveness of innovative processes through the ratio of innovative products output volume to the amount of expenditure on innovation. This calculation method made it possible to establish that SMEs demonstrate the greatest efficiency in a number of areas that are important in terms of ensuring the country’s technological sovereignty and import substitution.